1991
DOI: 10.1200/jco.1991.9.8.1476
|View full text |Cite
|
Sign up to set email alerts
|

Objective antitumor activity of acivicin in patients with recurrent CNS malignancies: a Southwest Oncology Group trial.

Abstract: Acivicin (AT-125) is a glutamine antagonist with dose-limiting, schedule-dependent CNS toxicity and predictable CSF penetration after intravenous administration. Because of these properties, a trial in CNS malignancies was initiated. Thirty-two patients with recurrent or residual malignant astrocytomas were treated with AT-125. The majority of patients had glioblastoma multiforme (24) and had received prior nitrosoureas (21). The median age was 50 years, and Southwest Oncology Group (SWOG) performance status w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…Acivicin efficiently reduced metastatic disease in the B16F10 mouse melanoma model (41) and has been tested in a number of clinical trials for both solid and liquid tumors. The results from these studies show some patient responses in non-small-cell lung carcinoma (42,43) and astrocytoma (44) but no response in relapsed or refractory acute leukemia (45), hepatocellular carcinoma (46), or ovarian carcinoma (47). Intermittent responses, severe central nervous system side effects, and myelosuppression and its reported ability to increase the formation of pancreatic cancer in rats (48) have limited the further development of this compound.…”
Section: Discussionmentioning
confidence: 99%
“…Acivicin efficiently reduced metastatic disease in the B16F10 mouse melanoma model (41) and has been tested in a number of clinical trials for both solid and liquid tumors. The results from these studies show some patient responses in non-small-cell lung carcinoma (42,43) and astrocytoma (44) but no response in relapsed or refractory acute leukemia (45), hepatocellular carcinoma (46), or ovarian carcinoma (47). Intermittent responses, severe central nervous system side effects, and myelosuppression and its reported ability to increase the formation of pancreatic cancer in rats (48) have limited the further development of this compound.…”
Section: Discussionmentioning
confidence: 99%
“…Acivicin, the most potent inhibitor of GGT that has been tested clinically, is a neurotoxin (18). The neurotoxicity of the glutamine analogues may be due to interference with glutamine in recycling the neurotransmitter glutamate via the glutamate-glutamine cycle.…”
mentioning
confidence: 99%
“…In the report of a phase II clinical study with acivicin, a reversible neurological toxicity was observed in patients with recurrent high-grade astrocytoma, indicating insufficient GGT selectivity and activity of acivicin (Olver et al, 1998). Another study reported that acivicin caused a neurotoxicity that made subjects depressed and hallucinate (Taylor et al, 1991). These negative results found in two clinical studies with acivicin strongly suggest that a high level of selectiveness is required for it to be used as a GGT inhibitor in vivo because these side effects are caused by nonspecific actions of acivicin that inhibits not only GGT activity but also other enzymes involved in nerve stimulation.…”
mentioning
confidence: 99%